Approaches to welfare technology in municipal eldercare. Issue 3 (2nd July 2020) - Frennert, Susanne
Abstract: Welfare technologies have been proposed in Scandinavian countries as way to ensure accessible and efficient care to those who need it. Significant investments have been made to develop and deploy these technologies. This study used a multiple case study design to explore how welfare technologies are implemented in Swedish eldercare practices. The multiple case study generated detailed knowledge and insights from a broad perspective on the employment of welfare technologies within various municipalities. The study revealed three approaches for integrating welfare technologies into municipal eldercare services: as an end-product, as a project, and as a strategy. Findings indicate that municipal welfare technology practices are diverse and multifaceted, yet implementing such practices is a complex process. This study proposes a focus shift, from technological solutions to organizational context, eldercare personnel, and care receivers.